2016
DOI: 10.1111/ajt.13885
|View full text |Cite
|
Sign up to set email alerts
|

En Bloc Liver Kidney Transplantation Using Donor Splenic Artery as Inflow to the Kidney: Report of Two Cases

Abstract: The number of simultaneous liver-kidney transplants has been increasing. This surgery is associated with an increased risk of complications, longer duration of surgery and longer ischemia time for the renal allograft. Two patients listed for liver-kidney transplant at our center underwent en bloc combined liver-kidney transplantation using donor splenic artery as inflow. Patient 1 previously underwent cardiac catheterization that was complicated by a bleeding pseudoaneurysm of the right external iliac artery t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…An additional concern is the potential risk to both grafts if the common arterial inflow is compromised via stenosis or thrombosis. 4 Although we did not experience this complication involving both organs in our cohort, there was one patient who had kinking of the splenic artery supply to the kidney, which may have contributed to the loss of the graft, although the same pa- Another limitation of the en bloc technique is the inability to perform a delayed kidney graft implantation, which has been increasingly utilized in patients with significant hemodynamic instability, vasopressor requirements, or coagulopathy during liver implantation. 15 For candidates who are at higher risk of hemodynamic instability, perhaps those who are already on vasopressors, are coagulopathic preoperatively, or have a difficult hepatectomy secondary to prior upper abdominal surgery or portal vein thrombosis, the traditional SLKT technique allowing for delayed implantation of the kidney should be considered.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…An additional concern is the potential risk to both grafts if the common arterial inflow is compromised via stenosis or thrombosis. 4 Although we did not experience this complication involving both organs in our cohort, there was one patient who had kinking of the splenic artery supply to the kidney, which may have contributed to the loss of the graft, although the same pa- Another limitation of the en bloc technique is the inability to perform a delayed kidney graft implantation, which has been increasingly utilized in patients with significant hemodynamic instability, vasopressor requirements, or coagulopathy during liver implantation. 15 For candidates who are at higher risk of hemodynamic instability, perhaps those who are already on vasopressors, are coagulopathic preoperatively, or have a difficult hepatectomy secondary to prior upper abdominal surgery or portal vein thrombosis, the traditional SLKT technique allowing for delayed implantation of the kidney should be considered.…”
Section: Discussionmentioning
confidence: 89%
“…Caution may be required when considering the use of en bloc SLKT for donors with aberrant renal or hepatic arterial anatomy. An additional concern is the potential risk to both grafts if the common arterial inflow is compromised via stenosis or thrombosis . Although we did not experience this complication involving both organs in our cohort, there was one patient who had kinking of the splenic artery supply to the kidney, which may have contributed to the loss of the graft, although the same patient also experienced antibody‐mediated rejection.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Gunabushanam et al reported two successful case reports of en bloc liver-kidney transplants using the splenic artery as inflow to the kidney allograft. In these cases, the renal artery was positioned posterior to the portal vein and bile duct, but anterior to the donor IVC [ 9 ]. In our case, the renal artery was positioned posterior to the portal vein and donor IVC.…”
Section: Discussionmentioning
confidence: 99%